THE UTILIZATION OF RICE PADDY MAPPING TECHNOLOGY AS A FOUNDATION FOR SUSTAINABLE FOOD AGRICULTURE PLANNING - Saputra, Janu Hidayat; Adlika, Nur Meily; Christanto, Ludovicus Manditya Hari (GEOREFERENCE, 2025)
Increasing demand for land is driving up the rate of agricultural land conversion. This may threaten the availability of paddy fields and thus food availability and security. This research aims to map the distribution of paddy fields to be planned as Sustainable Food Agricultural Land in Sengah Temila District, Landak Regency. In this research, the survey method was used with the population being all paddy field land use in Sengah Temila Sub-district with a total sample size of 100 land samples. The results showed that the total area of existing paddy fields in Sengah Temila Sub-district in 2024 based on Landak District Paddy Field was 5,040.69 ha. Through the agricultural information obtained using ground check technique and then processed using map overlay technique to obtain LP2B plan map, the existing paddy field area in Sengah Temila sub-district is 5,225.10 ha. The overlay results show that the land that can be planned as sustainable food agriculture land in Sengah Temila sub-district is 5,069.22 ha spread over each village. The LP2B plan in Sengah Temila Sub-district in this study is expected to be able to reduce the conversion rate of rice fields in order to achieve food security and sovereignty.